Dissatisfaction with body weight - Almeida, Ana Marques De (2004)
Objectives: To determine the proportion of USF Horizonte patients unsatisfied with their weight and the relative risk for dissatisfaction; to assess satisfaction in body mass index (BMI) classes and weight perception; to determine de prevalence of BMI classes and the proportion of counselling for weight change by the family doctor. Methods: Descriptive study of 400 adult patients (convenience sample). A questionnaire and an anthropometric evaluation were performed by the family doctor. Response rates, variables description, chi-square testing and logistic regression were performed. Results: Response rate: 96.8%. Very dissatisfied 14%, dissatisfied 3.7%, indifferent 10%, satisfied 33.3%, very satisfied 5.8%. Females were more dissatisfied than men. The relative risk for dissatisfaction was higher in females, younger ages, higher school level and BMI higher than 30 Kg/m2. Low weight 4.3%, normal 29%, excess weight 42.3%, obesity 24.6%. 47.1% low weight individuals, 42.6% with excess weight and 13.3% obese were satisfied. 62.8% of respondents correctly characterized their own weight. 43.2% of those who considered to have an adequate weight had excess weight, and 7.2% were obese. 33% were counselled to change their weight (32% with excess weight and 62.2% of the obese). Discussion/conclusions: Half of the sample was dissatisfied with its weight. Females were more dissatisfied. There was a high percentage of satisfied people who had an abnormal BMI. More than half of the sample had excess weight or obesity. There was a high correct assessment of one owns weight. The counselling of obese people was higher than in previous studies. Non-counselling is discussed. It is necessary to identify patients at risk for dissatisfaction taking up preventive measures and treatment of abnormal behaviour. Patients with abnormal BMI should receive counselling. Health education programs redefining beauty ideals, informing about desirable weight, should be implemented.